A new mathematical model for diagnosing chronic diseases (kidney failure) using ANN. Issue 1 (1st January 2018) - Almarashi, Adel; Alghamdi, Metib; Mechai, Idir
Abstract: In this paper, we introduce a new diagnosing technique for chronic kidney disease by using Artificial Neural Network (ANN). Where, the required data for the computational health-care system is collected from various hospitals at Jazan region, Saudi Arabia. Furthermore, in order to prove the convergence of this method, a ridge function is used in the hidden layer as a basis for the neurons. The technique applied for different number of neurons, and in each case a least square error is provided for choosing the best possible approximation.